Investigation of Dynamic Compaction and Vibro-compaction to Mitigate Liquefaction: A Case Study - Gouw Tjie Liong (Indonesian Geotechnical Journal, 2022)
Liquefaction is one of the phenomena that can be triggered by an earthquake. Earthquake causes an increase in pore-water pressure in soil, reducing soil’s effective stress to zero or near-zero. In this state, the soil loses its strength and behaves like a liquid. This is known as liquefaction. When soil loses its strength, so it also loses its bearing capacity, causing damage or failure to structures. The soil type that is most prone to liquefaction is loose saturated fine sand. Such soil can be found in many of coastal areas in Indonesia. Indonesia is also one of the most earthquake prone countries in the world, hence liquefaction is one of the natural hazards that Indonesia has to face. Earthquake cannot be prevented, and its occurrence cannot be accurately predicted. Fortunately, liquefaction can be prevented by doing soil improvement to increase the sand density. The two most commonly used ground improvement techniques to increase sand density is dynamic-compaction and vibro-compaction. A case study from Aceh province, where both ground improvement techniques were used, is presented in this paper to compare the performance of dynamic compaction and vibro-compaction.